Upaya pengembangan usaha mikro,kecil dan menengah (umkm) ditengah pandemi covid-19 dengan memanfaatkan e-commerce - Ramadhan Irwansyah; Puguh Setyo; Khusnul Fikri (Jurnal Pengabdian UntukMu NegeRI, 2022)
KKN from villages for this country aims to increase the economic value of MSME actors through digital marketing in the midst of the Covid-19 pandemic, Sungai Sibam Village. This KKN uses the method of explanation, discussion and practice. The explanation method is carried out by conveying material related to digital marketing directly to MSME actors. Discussion method, interaction between two or more people who discuss basic science. This method is to facilitate MSME actors who want to ask for material that has not been understood. In the practical method of implementation by applying the knowledge that they already have, namely practicing how to use online media as a means of product marketing. The results of this KKN show that efforts to increase the economic value of MSME actors through digital marketing in the midst of the Covid-19 pandemic are focused on 5 things, namely problem identification, the importance of branding and business legality, product packaging, attractive catalogs and advertisements